+0  
 
0
59
1
avatar

https://imgur.com/a/0YWCFAH

 Dec 19, 2018
 #1
avatar+98044 
+1

3 x^2 - 42   =   1 / 3x

 

Note that the term on the right side can be written as 3-x

 

So   we have

 

3 x^2 - 42  = 3 -x

 

Since the bases are the same, we can solve for the exponents

 

x^2 - 42 = - x       add x to both sides

 

x^2 + x - 42 = 0       factor

 

( x + 7) ( x - 6) =  0

 

Setting each factor to 0 and solving for x produces  the integer solutions

 

x = -7    or    x = 6

 

 

 

cool cool cool

 Dec 19, 2018

41 Online Users

avatar
avatar
avatar
avatar
avatar
avatar